Kepemimpinan Kepala Sekolah dalam Meningkatkan Kompetensi Profesional Guru di SMPN 6 Bathin Solapan - Tati Wijaya (Departement of Mathematics Education, 2022)
This study aims to describe the Role of the Principal's Leadership in Improving the Professional Competence of Teachers at SMP Negeri 6 Bathin Solapan. In this study the authors chose a qualitative descriptive approach, which is a research process that produces descriptive data either in the form of writing or expressions obtained directly from the field or research area about the leadership role of school principals in improving teacher professional competence at SMP Negeri 6 Bathin Solapan. The results of the study are First, the role of the principal as an administrator is shown by paying attention to class administration, school administration, facilitating learning media, facilitating school facilities and infrastructure. Second, the role of the principal as a supervisor is quite good, carrying out academic supervision starting from supervising learning tools, implementing teaching and learning activities, and discussing the results of the supervision that has been carried out. Third, the role of the principal as a manager is shown by making school programs, making programs of activities to increase the professional competency of teachers in schools, compiling the organizational structure of each activity and explaining the limits of their responsibilities, analyzing problems with teachers and giving responsibility to personnel according to the tasks carried out. . Fourth, the role of the principal as a motivator is quite good, carrying out several innovations, namely managing the physical work environment, motivating staff to improve teacher professional competence, conducting harmonious communication with subordinates and giving rewards to outstanding teachers. Fifth, the obstacles faced by school principals are the lack of school operational costs, the teacher's residence which is quite far from school, and the majority of female teachers have children under five.